2022
DOI: 10.3389/fvets.2022.822165
|View full text |Cite
|
Sign up to set email alerts
|

C-Type Natriuretic Peptide Regulates the Expression and Secretion of Antibacterial Peptide S100A7 in Goat Mammary Gland Through PKG/JNK/c-Jun Signaling Pathway

Abstract: During infection, the infected tissue secretes a variety of endogenous peptides to resist further invasion of pathogens. Among these endogenous peptides, the natriuretic peptides and the antimicrobial peptides attracted the most attention. C-type natriuretic peptide (CNP) and its receptor natriuretic peptide receptor B (NPR-B) were members of the natriuretic peptide system. The antimicrobial peptide S100A7 plays an important role to resist infection of bacteria in mastitis. It is reported that the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Considering estradiol is the most important and most biologically active hormone in estrogen [ 10 ], gMECs were treated with estradiol to explore the relationship between S100A7 and estradiol. According to recent research, LPS (5 μg/mL) can induce the synthesis and secretion of S100A7 in gMECs for 6 h. LPS also induced the expression and secretion of S100A7 in the present study, which supports the previous research [ 24 , 28 ], so we used it as a positive group at this point in the whole experiment. gMECs were further treated with different estradiol concentrations for 6 h. Interestingly, the expression of S100A7 was significantly induced with estradiol treatment as well as S100A7 secretion, which supports the research that S100A7 was induced with estradiol treatment in bovine mammary epithelial cells [ 12 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Considering estradiol is the most important and most biologically active hormone in estrogen [ 10 ], gMECs were treated with estradiol to explore the relationship between S100A7 and estradiol. According to recent research, LPS (5 μg/mL) can induce the synthesis and secretion of S100A7 in gMECs for 6 h. LPS also induced the expression and secretion of S100A7 in the present study, which supports the previous research [ 24 , 28 ], so we used it as a positive group at this point in the whole experiment. gMECs were further treated with different estradiol concentrations for 6 h. Interestingly, the expression of S100A7 was significantly induced with estradiol treatment as well as S100A7 secretion, which supports the research that S100A7 was induced with estradiol treatment in bovine mammary epithelial cells [ 12 ].…”
Section: Discussionsupporting
confidence: 91%
“…In order to determine whether E2 can induce the expression of S100A7 in gMECs cultured in vitro, the isolated gMECs were treated with 1 nM, 10 nM, 100 nM E2 and/or LPS (5 μg/mL), respectively, for 6 h; LPS is a positive group which has been proved to induce S100A7 mRNA expression and secretion in gMECs [ 24 , 28 ]. Firstly, the concentrations of LPS and E2 had no significant effect on the cell viability of gMECs for 24 h ( Figure 4 A, p > 0.05), the original data of Cell viability(OD) is shown in Table S1 , which showed that they can be used for subsequent research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteosarcoma [29] Pancreatic cancer [30] Alzheimer's disease [31] Potential therapeutic target for acute myocardial infarction [32] Neurodegenerative diseases [33] Veterinary studies: Porcine reproductive and respiratory syndrome virus [34] Atopic dogs [35] Toxoplasma gondii infection [36] S100A7 (Psoriasin1) Psoriasis and inflammatory skin diseases [37] Squamous cell carcinomas and large cell lung carcinomas [38] Alzheimer disease [39] Wound healing process [40] Role in breast cancer [41] Veterinary studies: Mastitis in goat [42] Use of fecal calprotectin [43] Biological function and use as biomarker [44] Diagnosis of sepsis [45] S100A10 (Calpactin-1 Plasminogen receptor S100A10)…”
Section: S100a6 [Calcyclin (Cacy)]mentioning
confidence: 99%